IMPACT OF ENVIRONMENTAL COSTS, ENVIRONMENTAL PERFORMANCE AND ENVIRONMENTAL DISCLOSURE ON COMPANY VALUE IN BASIC MATERIALS SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR PERIOD 2017-2019 - Savira, Winnie; Handayani, Sri; Rumondang, Safrida; Lesmana, Iwan (Indonesian Journal of Accounting and Governance, 2022)
This study aims to determine the effect of environmental costs, environmental performanceand environmental disclosure on company value. A number of previous literatures have found asignificant positive effect of the implementation of each of the three variables on company value, butthe number of studies examining the impact of these three variables on company value is still limited,while stakeholders are straving on sustainable reporting, this research can be able to emphasize theimportance of sustainable reporting. We build this research model based on environmentalcommitment, legitimacy theory and signal theory. Data testing is done by using the regression methodin testing the effect of these three variables on company value. The results showed that environmentalcost has significant positive impact to company value, environment performance has negative notsignificant impact to company value and environmental disclosure has positive impact but notsignificant to company value. In other result for the regression model that used in this research showedthat the model can significantly predict the dependent variable.